Low molecular weight heparin for intravenous drug users with deep vein thrombosis. Issue 6 (20th October 2004) - Russell, Michael; Dawson, Deborah
Abstract : A short cut review was carried out to establish whether low molecular weight heparins were safer and more effective anticoagulants than coumarins in injecting drug users (IDUs) with deep venous thrombosis (DVT). Altogether 276 papers were found using the reported search, of which two presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these best papers are tabulated. A clinical bottom line is stated.